The Benefits of Inspiratory Muscle Training in Heart Failure Patients – A Systematic Review - Katsoula, Christina; Vasileiadis, Ioannis; Routsi, Christina; Nanas, Serafeim; Karatzanos, Eleftherios (Health & Research Journal, 2022)
Background: Patients with heart failure (HF) have impaired function of respiratory system and frequently experience dyspnea. Inspiratory muscle training (IMT) offers an alternative way of exercise with a lot of benefits for HF patients. Aim: The aim of this review was to summarize and to reveal the effects of IMT in HF patients. Methods: Electronic searches were performed using Pubmed Database, Physiotherapy Evidence Database (PEDro) and Cochrane Library. Inclusion criteria were: RCTs, patients with HF, full text articles after 2010 and at least one intervention group with IMT. Methodological quality was assessed using the PEDro (Physiotherapy Evidence Database) scale. Results: Nineteen articles met the inclusion criteria and were included in this review. In most studies training protocols involved 3 to 7 sessions per week with intensity ≤30-60% of maximal inspiratory pressure (MIP), for a total duration of 4-12 weeks. Respiratory muscle strength improved in 11/12 studies, peripheral muscle strength in 4/5 studies, exercise capacity (peak VO2, VE/VCO2 slope) in 4/10, pulmonary function (FEV1, FEV1/FVC, FVC) in 0/5, functional capacity (6MWT) in 6/8, echocardiography parameters in 1/6, quality of life and dyspnea in 9/16. Control groups followed sham IMT, usual care, no intervention, intervention without exercise, or aerobic training, which could explain in some cases the conflicting results. Conclusions: IMT is beneficial for HF patients and should be included as a complementary method in cardiac rehabilitation programs. The optimal characteristics of ΙΜΤ as well as the benefits when combined with common forms of exercise need further research.